Design and investment of high voltage nanodielectrics - Mohamed, Ahmed Thabet, 1974- (Advances in computer and electrical engineering (ACEE) book series., 2021)
"This book examines the principle properties to the principle nanoparticles and its impacts on the fundamental polymers' properties"--